The tutorship of talented people in literary writing_ methods and programs: Examples from the United Arab Emirates - Alhashemi, Badeeah (Al-Adab Journal, 2025)
Talent is a readiness that is born with a person who has the ability to distinguish himself in one area of ​​life, or in several ones.  it requires making great efforts in order to discover them, appreciate them, support them and take care of them, with the aim of developing them.  Recent decades have witnessed the interest of developed countries in the talented people in various fields and allocated special budgets in order to develop methods of identifying them, and to design programs and initiatives studies to take care of them, which guarantees them an integrated psychological, mental and social growth.  The UAE has spared a noticed effort in this field. This research is focusing the light on the most prominent initiatives and programs implemented by the country’s institutions with the aim of discovering talented citizens in the field of literary writing, tutorship them and refining their creative talent.  This is done through three axes: the first deals with the concept of creative writing, and talent development and nurturing programs.  The second: reviews a number of programs for the talented children in creative writing. The third focuses on the sponsorship programs for the talented youth in the same field.